A 'community criminology' : perceptions of crime and social control amongst Bradford Pakistanis - Bolognani, Marta (2006)
Despite the undeniable significance of the `race and crime' stream in criminology, knowledge held by minority ethnic groups on these matters is still much overlooked. It is this gap in the literature that this thesis begins to fill, based on both fieldwork and documentary research. The case-study through which the importance of minority ethnic views is investigated is a Bradford Pakistani one. The neglect by academic criminological accounts of a systematic analysis of minorities' views, and their cultural specificities, may be imputed in part to the fear of pathologisation. On the other hand, many media accounts seem to look at alleged `dysfunctionalities' of certain groups. After September 11th 2001 and July 7th 2005, Muslim communities seem particularly susceptible to negative stereotyping. The research looks at `cultural agency', avoiding ill-fitted generalisation and stereotypes based on an imposed essentialisation of the Bradford Pakistani community. This thesis analyses Bradford Pakistanis' perceptions of crime and its production, construction, sanctioning and prevention, through an `emic' approach. Thus, emic units are discovered by the analyst in the specific reality of a study and the social actors, rather than created by her/him a priori, or by imposing universal categories created for other settings. Through collecting perceptions around crime ethnographically, the research revealed that Bradford Pakistanis' perceptions of crime and control are a combination of the formal and informal, or British and `traditional' Pakistani, that are no longer separable in the diasporic context. The emic of cultural agency can be said to legitimise the term community criminology, but not in the sense that Bradford Pakistanis possess exclusive and monolithic criminological discourses, labelling, preventive strategies and rehabilitation practices. Rather, they engage with mainstream criminological and policy discourses in a way that might well be considered a kind of reflection representative of the position of their diaspora: community for them does not only include their traditional structures but all the intracommunal and intercommunal relations that are meaningful to them, both as resources and constraints